Fuzzy Logic Controller Implementation for Induction Motor Soft Start - Dhakal, Bibek; Nayak, Sagar; Rokaya, Sandip; Adhikari, Shashi (KEC Journal of Science and Engineering, 2026)
Direct-on-line starting of three-phase induction motors causes high inrush current, voltage dips, and torque oscillations, reducing motor life and system stability. Conventional soft starters like auto-transformers and star-delta systems offer limited efficiency and control. This paper proposes a fuzzy logic controller (FLC)-based soft starter for induction motors driving fan-type loads to achieve smooth, adaptive, and energy-efficient operation. The system, modelled in MATLAB/Simulink with optimized membership functions and rule bases, uses weighted average defuzzification for real-time voltage control. Simulation results show that the FLC reduces peak starting current to about 41 A, compared to 80 A in direct-on-line and 54 A in PI-controlled methods. The fuzzy-based system provides smoother torque and speed response, reducing mechanical stress and improving performance. Thus, FLC-based soft starters offer an efficient, scalable, and intelligent solution for industrial applications such as HVAC systems, pumps, and conveyors, with potential for future hardware implementation.